INFORMATION SYSTEM DESIGN OF TOURIST ATTRACTIONS IN THE WORLD - Lubis, Muhammad Azri Hadiansyah; Gultom, Felix Hotman Tua; Telaumbanua, Brian Marcelino; Zalukhu, Gratitude Arman; Lumban Gaol, Tonggo Andrean; Wenny Jodana (INFOKUM, 2023)
This research was conducted with the aim of designing and building a tourist information system that can present and provide information on tourist attractions and culture in the world. The background of this research was raised based on the need for an information system that can provide complete information quickly and accurately, because the delivery of information on tourist attractions in the world today still uses brochures, in other words delivery like this. information is not effective enough and has not been implemented. enough to attract tourists to visit tourist attractions in the world. And with this information system it can also make it easier for tourism and local culture to manage information on tourist attractions and culture in that place. This study uses the SDLC (System Development Life Cycle) method which consists of several stages, namely planning, analysis, design, implementation and maintenance of the system. So that it can be used easily by users to get the information services they need.